Analysis of Monitoring Performance by AMC Officers at Juwata Tarakan International Airport, North Kalimantan - Sultan Ali; Desiana Rachmawati (CV. Rayyan Dwi Bharata, 2023)
Every airport operator is required to provide facilities that meet the requirements for aviation safety and security. In order for airport facilities to function properly, the operator is required to carry out supervision within a predetermined period of time. Each airport is required to provide a Follow Me Car and provide parking stand supervision by AMC according to the applicable SOP. The purpose of this study was to determine and analyze the performance of supervision by AMC officers at Juwata Tarakan International Airport, North Kalimantan. The research used a qualitative descriptive approach, the research was conducted from September to October 2023 by conducting structured interviews with 3 informants, namely the person in charge of the unit, senior and junior AMC by using a data validity test. Secondary data is in the form of documents, books, journals and SOPs as supporting and complementary data for writing this research. Data analysis techniques used in this study are data reduction, data presentation, drawing conclusions and verification. Researchers use technical triangulation so that the data in this study proves its validity. Obstacles faced by AMC unit officers are the lack of AMC officers, lack of coordination between AMC officers and ground handling officers, and the absence of CCTV facilities in the parking stand area. These obstacles can be overcome by AMC officers coordinating with each other accompanied by the person in charge, conducting ramp checks on the apron once every 3 hours using a follow me car so that the parking stands are always safe and protected from dangerous goods, providing marshallers guiding the aircraft to the parking stands using the follow me car service.